PSYCHOLOGICAL-PEDAGOGICAL FACTORS OF IMPROVING THE LITERACY OF ELEMENTARY SCHOOL STUDENTS BASED ON A PERSONAL VALUE APPROACH (Academia Science Repository, 2023)
This article is written about psychological-pedagogical factors of improving literacy of school students on the basis of approaching to personal skills. In this way, the spiritual management of the knowledge of existence and the approach to personal value are directed, and the content determines the behavior and relations of the person. therefore, education can be seen as a process of internalization of socially organized universal values.